Associations Between Classroom Learning Environment and Students’ Outcomes - Akhmadaliyeva, Mukharramoy.Olimjon qizi.; Sotvoldiyeva, Hojirabonu. Hojiakbar qizi. (European Journal of Life Safety and Stability (2660-9630), 2023)
This article examines associations between classroom learning environment and students’ outcomes. Researches on this article are analyzed and reviewed in the essence.